2019
DOI: 10.1029/2019jc015576
|View full text |Cite
|
Sign up to set email alerts
|

Quantifying Eulerian Eddy Leakiness in an Idealized Model

Abstract: An idealized eddy-resolving ocean basin, closely resembling the North Pacific Ocean, is simulated using MITgcm. We identify rotationally coherent Lagrangian vortices (RCLVs) and sea surface height (SSH) eddies based on the Lagrangian and Eulerian framework, respectively. General statistical results show that RCLVs have a much smaller coherent core than SSH eddies with the ratio of radius is about 0.5. RCLVs are often enclosed by SSH anomaly contours, but SSH eddy identification method fails to detect more than… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
24
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 48 publications
2
24
0
Order By: Relevance
“…Some recent articles highlighted the inherent limitations of tracking mesoscale eddies through altimetry and/or with SSH‐based techniques (e.g., Amores et al., 2018; Stegner et al., 2021). In addition, the classic vision of materially coherent mesoscale eddies has been questioned over the last decade, emphasizing the leakiness of such structures (e.g., Cetina‐Heredia et al., 2019; Liu et al., 2019). Furthermore, as the resolution of numerical models and observations increases, emerging submesoscale three‐dimensional circulations seem to play a preponderant role in shaping material patterns in the surface layers (e.g., Lévy et al., 2018; Uchida et al., 2019).…”
Section: Summary and Discussionmentioning
confidence: 99%
“…Some recent articles highlighted the inherent limitations of tracking mesoscale eddies through altimetry and/or with SSH‐based techniques (e.g., Amores et al., 2018; Stegner et al., 2021). In addition, the classic vision of materially coherent mesoscale eddies has been questioned over the last decade, emphasizing the leakiness of such structures (e.g., Cetina‐Heredia et al., 2019; Liu et al., 2019). Furthermore, as the resolution of numerical models and observations increases, emerging submesoscale three‐dimensional circulations seem to play a preponderant role in shaping material patterns in the surface layers (e.g., Lévy et al., 2018; Uchida et al., 2019).…”
Section: Summary and Discussionmentioning
confidence: 99%
“…Thus, it is anticipated that these algorithms can be leveraged to compute CNOPs for more realistic models, paving the way for further exploration of paired eddies sensitivity in future studies. Furthermore, recent works have noted the significance of filamentary structures at the periphery of eddies in material transport (Liu & Abernathey, 2023; Liu et al., 2019). The findings of this study may hold important value for predicting material transport caused by eddies, presenting an interesting avenue for further research.…”
Section: Summary and Discussionmentioning
confidence: 99%
“…Moreover, Liu et al (2019), who quantified the material coherence of Eulerian SSH eddies and rotationally coherent Lagrangian vortices detected using the LAVD method, showed that SSH eddies are highly leaky and do not maintain their material coherence over the detection time interval, as opposed to the Lagrangian coherent vortices that were detected based on the LAVD method. They also showed that the SSH eddies may be coherent in their core, but they also may not, making SSH eddies almost indiscernible from any other body of water in the ocean, in terms of material coherence.…”
Section: Detection Of Coherent Eddiesmentioning
confidence: 99%